Power to participants: methodological and ethical reflections from a decade of adolescent advisory groups in South Africa. Issue 7 (3rd July 2021) - Cluver, Lucie; Doubt, Jenny; ,; Wessels, Inge; Asnong, Carine; Malunga, Samantha; Mauchline, Kerry; Vale, Beth; Medley, Sally; Toska, Elona; Orkin, Kate; Dunkley, Yasmin; et al.
ABSTRACT : Whilst the HIV response has made significant progress in increasing representation of adults affected by HIV, the meaningful inclusion of children and adolescents has lagged. But this may be a pivotal moment of change. We report on a decade of conducting adolescent advisory groups in South Africa, to reflect on youth advisory processes. Data was collected from 2008 to 2018 from adolescent advisors ( n = 60) and researchers ( n = 25), and included feedback sessions, social media, anonymous "post-boxes" and interviews. Findings include the value of adolescent involvement in multiple stages of research co-creation and engagement in policy processes, the need for a safe environment and supporting adolescents living in extreme vulnerability. We also discuss the reconfiguring of power and personal relationships, and logistical and financial needs of adolescent advisory groups. Findings suggest that adolescent co-creation of research is feasible, even with very vulnerable adolescents, although ethical considerations need to be carefully addressed. Benefits include increased methodological rigour, enhanced adolescent acceptability of research and the recalibration of research dynamics for the empowerment of their target beneficiaries. Future studies could benefit from meaningfully involving adolescents through youth advisory groups.